Advancing water footprint assessments: Combining the impacts of water pollution and scarcity - Éléonore Pierrat; Alexis Laurent; Martin Dorber; Martin Rygaard; Francesca Verones; Michael Hauschild (Science of The Total Environment, 2023)

Heat recovery and water reuse in micro-distilleries improves eco-efficiency of alcohol production - Isabel Schestak; Jan Spriet; Kirsty Black; David Styles; Maria Faragò; Martin Rygaard; A. Prysor Williams (Journal of Environmental Management, 2023)

Eco‐efficiency of water and wastewater management in food production: A case study from a large dairy in Denmark - Julie Skrydstrup; Sille Lyster Larsen; Martin Rygaard (Journal of Industrial Ecology, 2020)
Rising water demands and pressures on water resources call for water management in industrial production. An eco‐efficiency framework may provide justification for water consumption and treatment by combining environmental and economic dimensions in a life cycle perspective. We used principles of value added and value chain assessment (VCA) in the life‐cycle system boundaries for a consistent assessment of eco‐efficiency. The method was demonstrated for a membrane bioreactor‐based, decentralized wastewater treatment and reuse in a dairy. The LCA results showed that decentralized wastewater treatment and reuse in the dairy will improve the aquatic environment by 80% (freshwater) and 51% (marine water), but increase the negative impact on climate change by 27% compared to conventional wastewater treatment. The VCA revealed that the decentralized alternatives would increase the value added by 1.3–1.4 €/m 3 wastewater in the dairy, but also incur a value loss of 1.4–1.9 €/m 3 for associated stakeholders such as the centralized wastewater treatment plant. The case study revealed the critical nature of a well‐defined system boundary that includes impacts along the entire value chain and exposed pros and cons for decision‐makers at both the system level and individual stakeholder level.